Metode Penyimpanan Media Kontras Oral Nanopartikel Mangan Teh Oolong untuk Pemeriksaan Magnetic Resonance Cholangiopancreatography (MRCP) - Fatimah, Fatimah; Ardiyanto, Jeffri; Dartini, Dartini; Sugiyanto, Sugiyanto; Erfansyah, Muhammad (Poltekkes Kemenkes Semarang, 2025)
Background: MRCP examination using natural manganese contrast media cannot provide optimal images of gastroduodenal suppression covering the biliary system when compared with standard contrast media. Various studies on manganese contrast media have been developed, but not much has been linked to the use of natural manganese nanoparticles as an alternative contrast media. This study aims to prove that manganese nanoparticles extracted from oolong tea as an alternative oral negative contrast medium for MRCP examinations are thought to improve image quality and do not cause neurotoxic effects in healthy volunteers.Methods: The research design carried out was experimental research. The research included making extracts and making oolong tea nanoparticles, and each expired or unexpired ingredient was observed using organoleptic tests in terms of taste, color, texture, and aroma, at 30 days, 90 days, and 120 days.Results: This research shows that Mn nanoparticle oral negative contrast media for oolong tea experiences significant changes in taste, color, texture, and aroma with storage time. Oolong tea stored for 60 days has the best characteristics with a fresh taste, bright yellow color, and smooth texture. After 90 days, the taste starts to become sour and bitter, with a grainy texture. 120 days of storage produced tea with a very sour and bitter taste, as well as a rough texture that the panelists didn't like. Organoleptic tests showed that panelists preferred 60-day (T1) oolong tea based on taste, color, texture, and aroma. Storage at a temperature of 4-25Â°C and paper sack packaging is more effective in maintaining tea quality.Conclusions: Storage of oolong tea with Mn nanoparticles shows that tea stored for 60 days has the best quality. Tea stored for 90 days begins to degrade, and after 120 days it is disliked because of its sour and bitter taste. Temperatures of 4-25Â°C and paper sack packaging are effective in maintaining tea quality.